Allogeneic adipose-derived stem cells promote ischemic muscle repair by inducing M2 macrophage polarization via the HIF-1α/IL-10 pathway. (4th August 2020) - Liu, Junchao; Qiu, Peng; Qin, Jinbao; Wu, Xiaoyu; Wang, Xin; Yang, Xinrui; Li, Bo; Zhang, Wenjie; Ye, Kaichuang; Peng, Zhiyou; Lu, Xinwu
Abstract: Adipose-derived mesenchymal stem cells (ASCs) are multipotent stromal cells that possess considerable therapeutic potential for tissue remodeling. However, their protective mechanism in critical limb ischemia has not been fully defined. After the occlusion of blood vessels, hypoxia becomes a prominent feature of the ischemic limb. This study investigated the immunomodulatory effect of ASCs on ischemic muscle repair and explored the specific mechanism. We found that the ability of RAW264.7 cells to migrate was impaired in hypoxia, whereas coculturing with ASCs could enhance the migration capacity. In addition, under hypoxic conditions, the paracrine effect of ASCs was enhanced and ASCs could induce RAW264.7 macrophages toward the anti-inflammatory M2 phenotype. We further demonstrated that ASCs-derived interleukin 10 (IL-10), mediated by hypoxia inducible factor-1α (HIF-1α), played a crucial role in the induction of M2 macrophages by activating the signal transducer and activator of transcription 3 (STAT3)/Arginase (Arg-1) pathway. Our in vivo experiments revealed that transplanted ASCs exhibited an immunomodulatory effect by recruiting macrophages to ischemic muscle and increasing the density of M2 macrophages. The transplantation of ASCs into ischemic limbs induced increased blood flow reperfusion and limb salvage rate, whereas the depletion of tissue macrophages or transplanting HIF-1α-silenced ASCs inhibited the therapeutic effect. These findings elucidated the critical role of macrophages in ASCs-mediated ischemic muscle repair and proved that allogeneic ASCs could exert the protective effect by enhancing the recruitment of macrophages and inducing macrophages toward M2 phenotype through HIF-1α/IL-10 pathway. : Abstract : Allogeneic adipose-derived mesenchymal stem cells (ASCs) exert therapeutic effect in ischemic muscle by enhancing tissue macrophages recruitment and inducing M2 macrophages polarization. Mechanically, ASCs-derived IL-10, mediated by HIF-1α, plays a crucial role in the induction of M2 macrophages by activating STAT3/Arg-1 pathway.